IMPLEMENTATION OF THE DISCREPANCY MODEL IN THE ZIYADAH AND MUROJAAH PROGRAMS AT MTS NEGERI 1 PURWOREJO - Suswati; Muhlil Musolin (CV. Fahr Publishing, 2025)
This study aims to evaluate the implementation of the Ziyadah and Murojaah programs at MTs Negeri 1 Purworejo using the Discrepancy evaluation model. The primary objective is to identify the gap between established program standards and actual field implementation. A formative evaluation approach with a mixed-methods design was employed, integrating both quantitative and qualitative data. Data collection techniques included surveys, in-depth interviews, field observations, and document analysis. The study participants consisted of students, tahfidz instructors, and program administrators selected through purposive sampling. Findings revealed that while the input and process components of the program were implemented as planned, significant discrepancies were found in the output aspect, particularly in independent revision (murojaah) and time management. Students’ memorization achievement reached only about 70% of the targeted level. Identified challenges included limited time allocation, lack of diverse teaching methods, low monitoring frequency, and underutilization of technology in supporting memorization activities. The study concludes that the Discrepancy model is effective for systematically evaluating religious-based educational programs and providing practical improvement strategies. Furthermore, the study contributes new insights to the Islamic education evaluation literature by addressing the specific needs of tahfidz programs and proposing adaptive strategies that align with the characteristics of today’s learners.